PENGARUH PERTUMBUHAN EKONOMI DAN JUMLAH PENDUDUK TERHADAP PENDAPATAN ASLI DAERAH (PAD) KABUPATEN SANGGAU TAHUN 2004-2011 - B01109088, JUPRIADI (Jurnal Pembangunan dan Pemerataan, 2014)
This study, entitled "Effects of Economic and Population Growth on Local Revenue Sanggau Year 2004-2011", which aims to "determine and analyze the influence of economic growth at constant 2000 prices GDP indicator and the number of people partially or simultaneously to local revenues Sanggau ". The method used to analyze the relationship is linear regression method, using secondary data obtained from the time series of publications Central Statistics Agency (BPS) and the Financial Bureau of West Kalimantan Province. The results of the calculations and the data analisisi, it was explained that the economic growth indicators of GDP at constant 2000 prices significantly (2.548> 1.699), and the number of residents was not significant (-0.159 <Â± 1.699) affect local revenue receipts Sanggau at 95% confidence level. For the F test can be summed up with the economic growth indicators of GDP at constant 2000 prices and population simultaneous effect on local revenues Sanggau at 95% confidence level and have a very strong and direct views of the value of multiple correlation (R) of 0.879 is close to 1 . For R2 with a value of 0773 which showed that economic growth at constant 2000 prices GDP indicator and the number of the population has a considerable influence on the acceptance of local revenues Sanggau because the value of R2 close to 1. The low level of education and human resources most people in the population signifies less productivity Sanggau. It should be a special attention and immediately followed up, because with the increased productivity of the population will certainly have a positive impact to the economy and acceptance of PAD in Sanggau, due to rising income levels will increase the ability of people to pay the tax itself be a source of revenue. Keywords: Economic Growth, Population, Revenue (PAD).